Spectrophotometric Methods for the Determination of Indinavir Sulphate - Sarma, C.S.N.; Madhava Sarma, D.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (A, B and C) have been developed for the estimation of indinavir sulphate in the bulk and dosage forms. Method A, involves the addition of excess chloramine-T of known concentration in acidic medium to indinavir sulphate and determination of un-reacted chloramine-T by measure of decrease in the absorbance of dye gallocyanine (GC, λmax 540 nm). Method B is based on the reduction of heteropolyacid, phosphomolybdotungstic acid, (FC) reagent by indinavir sulphate producing a characteristic intense blue colour (λmax 760 nm). Method C is based on the charge-transfer complex formation between indinavir sulphate and chloranil (λmax 540 nm). Regression analysis, Beer's law plots showed good concentration ranges of 2.5-20, 2-25 and 4.5-40 μg/mL for methods A, B and C, respectively.